2010
DOI: 10.1158/0008-5472.can-09-2899
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase-7 and Premalignant Host Responses in Helicobacter pylori–Infected Mice

Abstract: Helicobacter pylori-induced gastritis is the strongest singular risk factor for gastric adenocarcinoma. Matrix metalloproteinase-7 (MMP-7) is a proteolytic enzyme that can modify the intestinal microbial replicative niche as well as affect tumorigenesis, and H. pylori stimulates expression of MMP-7 in gastric epithelial cells in vitro.Utilizing a transgenic murine model of H. pylori-mediated injury, our experiments now show that gastric inflammation is increased within the context of MMP-7 deficiency, which in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…Our previous studies using a mouse model of H. pylori -induced gastritis demonstrated that MMP7 −/− C57BL/6 mice develop more severe inflammation in response to H. pylori infection than wild-type (WT) C57BL/6 mice 5 . To extend these findings and identify mechanisms that regulate this phenotype, WT C57BL/6 and MMP7 −/− C57BL/6 mice were challenged with broth alone as an uninfected control or the H. pylori strain PMSS1, and stomachs were harvested and analyzed 12 weeks post challenge.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous studies using a mouse model of H. pylori -induced gastritis demonstrated that MMP7 −/− C57BL/6 mice develop more severe inflammation in response to H. pylori infection than wild-type (WT) C57BL/6 mice 5 . To extend these findings and identify mechanisms that regulate this phenotype, WT C57BL/6 and MMP7 −/− C57BL/6 mice were challenged with broth alone as an uninfected control or the H. pylori strain PMSS1, and stomachs were harvested and analyzed 12 weeks post challenge.…”
Section: Resultsmentioning
confidence: 99%
“…One host response that augments the risk for gastric cancer is increased expression of the proinflammatory cytokine IL-1β, and individuals who harbor high-expression IL-1 β alleles are at increased risk for gastric cancer 4 . Another host factor linked to neoplasia within the intestinal tract is matrix metalloproteinase 7 (MMP7), a minimal-domain MMP secreted preferentially by epithelial cells 58 . Previously, we observed that C57BL/6 mice lacking MMP7 develop increased inflammation following H. pylori infection, although the specific mechanism regulating this phenotype was not identified 5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activated DCs are induced by CagA, but mainly by CagE, to release high amounts of IL-23 and IL-1 thus inducing the expansion of CD4+ Th17 T cells [54] which might exert an anti-inflammatory role [55] and a role in vaccine induced immunization [56]. Mast cells (MC) [57] and matrix metalloproteinase-7 (MMP-7) [58] were suggested to regulate Th17-dependent inflammatory response to H. pylori infection. Dotted lines represent inhibitory effects and continuous lines stimulatory effects.…”
Section: Helicobacter Pylori Induced Chromosomal Instability Geneticmentioning
confidence: 99%
“…The matrix metalloproteinases (MMPs) family, which can degrade the extracellular matrix, is the most important group of proteolytic enzymes and is mostly produced by the interstitial cells. MMP-7 is relatively unique because it is mainly produced in epithelial cells (4). In the past, research about the relationship between MMP-7 expression and Lauren classification in gastric cancer has been quite inconsistent.…”
Section: Introductionmentioning
confidence: 99%